Preparation and Photocatalytic Activity of Mesoporous TiO2 Microspheres - Mao-Xiang, Jing; Xue-Qin, Jiang; Wang-Xing, Li; Dong-Hong, Li; Zhou, Wang (Micro and Nanosystems, 2009)
Mesoporous TiO2 microspherical photocatalyst was prepared through a novel continuous precipitation method using Titanous sulphate and ammonium bicarbonate as raw materials. After calcination at 700 °C, the as-prepared TiO2 sample showed anatase with spherical or spheroidal morphologies,large particle size of 5 to 30μm,crystallite size of 9.4nm, specific surface area ∼138m2/g, and narrow pore size distribution with pore radius in the range of 2 to 5nm.In addition, this sample shows excellent photocatalytic activity to degrade phenol solution and good sedimentation to recover TiO2. The mesoporous TiO2 microspheres can be widely used as a photocatalyst in moving or fluidized bed reactors to treat organic waste waters.
Keywords: photocatalyst